Meraih Derajat Sehat Bagi Lansia dalam Perspektif Islam - Waharjani, Waharjani; Jailani, Mohammad; Maki, Hud Leo Perkasa (Analisis: Jurnal Studi Keislaman, 2023)
The importance of living a healthy life, keeping the body fit in worship is everyone's dream, including the elderly. However, a special problem for the elderly is the natural process of aging which has an impact on the physical, mental and social relations of the elderly. Therefore this study seeks to find solutions related to achieving a healthy life for the elderly from an Islamic perspective. This study uses qualitative research methods that are descriptive analysis, data sources obtained through interviews and documentation, data analysis techniques through data reduction, data display, and data verification. The analytical knife in this study uses a triangulation technique. The results of these findings indicate the importance of practicing the concept of a healthy and happy life based on the directions and instructions of the Koran and hadith. Abdullah Nasih Ulwan provides alternatives and ways that lead to a healthy and happy life even in old age through five pillars: al-Qudwah, al-'Adah, al-Mauidha, al-Mulahadah and al-Uqubah.